“We’re experts in everything and specialized in almost nothing”: professionals dealing with GBV on the aftermath of FGM/C in a Lisbon municipality” - Falcão, Ricardo (International Forum Female Genital Mutilation - Exploring strategies and good practices - From local global, 2018)
This essay conceptualizes an approach to prevention and knowledge production in the context of a project focused on gender-based violence, social construction of gender, cultural transmission, and harmful traditional practices, among migrants from Guinea-Bissau, youth and adult, men and women and professionals accompanying them. I will try to put in a critical perspective the views mostly held by these professionals working in social and community intervention, concerning the development of participatory, community-level, bottom-up projects, with a specific focus on gender and gender-based violence. How projects are developed, which obstacles they find, how coherent and consolidated is the strategy employed, will be main points of discussion. Struggling with lack of institutional memory, rotation of civil servants inside public administration, lack of specific training, but also with normative approaches to FGM/C prevention, these professionals ‘learn as they do’. The project was developed in a municipality belonging to the Lisbon Metropolitan Area where previous work on FGM/C existed. Despite three previous projects where the FGM/C question has arisen (and at least two of them tried to address it straightforwardly), the subject has been abandoned as single focus. The reasons behind this drop out of focus of FGM/C are directly concerned with certain normative approaches to prevention, but also to multiple institutional constraints that are surprisingly not so much financial issues but rather organizational ones. By presenting the current project as a departure from FGM/C, whilst explaining how FGM/C came to be a focus in the first place, I intend to shed some light on a less visible part of project development, as dependent on individuals rather than consolidated institutional approaches. Making use of ethnographic methods and participation, I have accompanied this project from its inception, still as an idea, to its implementation, through to its conclusion, being allowed to freely engage with all participants, professionals and population.